IDEA AND PERSONA REPRESENTATION OF THE 2024 INDONESIA PRESIDENTIAL CANDIDATES: A SYSTEMIC FUNCTIONAL LINGUISTICS CASE STUDY - Salsabila, Aghnia (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
To achieve an ideal democratic process, voters need to have sufficient information about every candidate before making a well-informed decision. To understand the candidates’ values, one can look at their particular language choice which is realized in their idea representations from text elements (vision and mission statement) and persona representations from visual elements (campaign posters). Combining two theoretical frameworks, Systemic Functional Linguistics and The Grammar of Visual Design, this research aims to explain how presidential and vice presidential represent their ideas and personas through vision and mission and campaign posters in the 2024 Indonesia Presidential Election. Finding shows SFL and Visual Design Grammar can explain how politicians reflect their thought and ideas into set of material and mental clauses while supporting the clauses with respective posters, as shown by Candidate 1 and Candidate who enhance their ideas with a coherence visual elaboration, meanwhile Candidate 3 do not show idea and persona congruity in their texts and image representations